Development of anthracnose resistant chili varieties through marker-assisted pedigree selection - Ridzuan, Raihana (2018)
Capsicum annuum (chili) is one of the most valuable vegetable crops worldwide. However, the quality and yield production of this crop is facing a significant challenge due to the most destructive fungal disease namely anthracnose. As results of anthracnose disease infection in chili production in Malaysia, this study was conducted to develop high yield and anthracnose resistant C. annuum genotypes through marker-assisted pedigree selection. The specific objectives of this study were to evaluate morpho-physiological and yield performances of 14 chili genotypes over two planting seasons, to determine virulent Colletotrichum species via pathogenicity test as well as to identify their species using morphological and molecular characteristics, to select parental lines based on anthracnose disease severity, biochemical content and antioxidant activity for crossing program, to identify SSR markers linked to anthracnose resistance in the parental, F1 and F2 populations, and to select high-yielding and anthracnose resistant genotypes in F2 population. This study consists of four experiments, where in the first experiment on field evaluation of 14 genotypes, genotype AVPP9813 indicated the highest number of fruits and total yield per plant (130.13 fruits and 541.39 g) followed by Kulai 907 and Chili Bangi 5, (99.63 fruits, 502.64 g) and (110.00 fruits, 418.46 g) respectively. The highest genotypic (GCV) and phenotypic coefficient of variation (PCV) were shown by the fruit number per plant (49.71% and 66.04%, respectively). High heritability was observed in yield characters; fruit weight, length and girth and indicated high genetic advance. A total of eight groups were obtained from the cluster analysis. In the second experiment, five virulent isolates were successfully selected according to their degree of virulence with more than 15% anthracnose severity lesion (anthracnose severity score 7). The phylogenetic analyses from DNA sequence data based on the ITS regions clearly grouped three isolates as C. truncatum, one isolate as C. fructicola, and another one isolate as C. sojae with bootstrap support 100%, 98% and 100% respectively. In the third experiment, the responses of ripe fruits of 14 selected chili genotypes on these virulent Colletotrichum species revealed the resistance of genotypes SDP203-6-3, AVPP0009, AVPP0514, AVPP0705, AVPP0805 and AVPP9813 against all isolates with less than 2% anthracnose lesion (anthracnose severity score 1). In case of biochemical experiment, the capsaicinoids content and total phenolic content were high in Chili Bangi 3 at ripe dry fruit while for antioxidant activity using beta carotene bleaching assay, SDP203 was the highest in ripe dry fruit. Two susceptible genotypes namely, Kulai 907 and Chili Bangi 3, and two resistant genotypes; AVPP0805 and AVPP9813 were selected for marker-assisted pedigree breeding program. In the fourth experiment, a total of 165 F1 crosses and reciprocal plants were screened with one SSR marker (Hpms 2-24) linked to anthracnose resistant genes. Out of the 165 plants, 72 plants were confirmed carrying resistance genes. These plants were evaluated for morphological and yield traits, and were challenged against the most virulent C. truncatum isolate (Genebank accession number: MG016494). In term of yield and yield performances, F1 hybrids especially Kulai 907 × AVPP0805 showed better results compared to those F1 reciprocal crosses which were good in growth performances. Further, 24 high yield and resistant F1 plants were selected and selfed to produce F2 generation. The chi-square analysis based on 283 individual plants from F2 population showed that it is no significance differences between observed and expected values with 1:2:1 ratio. This indicated that the anthracnose resistant gene is control by a single gene inheritance. Ten improved anthracnose resistant chili lines namely, AP-13, AP-18, AP-25, AP-37, AP-41, BP-23, BP-44, CP-36, DP-37, DP-51 and DP-57 were selected from F2 generation showing high yield and anthracnose resistant plants for further breeding program.